2019
DOI: 10.1080/00365521.2019.1566493
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitor use is associated with elevated faecal calprotectin levels. A cross-sectional study on subjects referred for colonoscopy

Abstract: Objectives: Faecal Calprotectin (FC) is a sensitive marker for gut inflammation. However, slightly elevated FC levels are also common in subjects without inflammation. We investigated the association between FC and clinical factors including concomitant use of medical therapy in patients with a normal colonoscopy. Material and methods: Outpatients (n ¼ 1263) referred for colonoscopy, performed FC test (CALPRO) the day before the start of bowel preparation. All subjects answered questionnaires that included que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 44 publications
4
45
2
3
Order By: Relevance
“…We found that PPI use was associated with increased intestinal inflammation. This has been previously described in the context of other diseases [65][66][67] and we have recently linked dysbiosis, gut permeability and intestinal inflammation to adverse outcome in patients with liver cirrhosis who use PPI [63]. Antihypertensive use was associated with slightly, but significantly elevated CRP levels, which is most likely due to the underlying disease and not to the drug itself, since arterial hypertension is associated with elevated CRP levels [68] and therefore validates the relevance of our findings although sample size is small.…”
Section: Discussionsupporting
confidence: 56%
“…We found that PPI use was associated with increased intestinal inflammation. This has been previously described in the context of other diseases [65][66][67] and we have recently linked dysbiosis, gut permeability and intestinal inflammation to adverse outcome in patients with liver cirrhosis who use PPI [63]. Antihypertensive use was associated with slightly, but significantly elevated CRP levels, which is most likely due to the underlying disease and not to the drug itself, since arterial hypertension is associated with elevated CRP levels [68] and therefore validates the relevance of our findings although sample size is small.…”
Section: Discussionsupporting
confidence: 56%
“…We found that PPI use was associated with increased intestinal inflammation. This has been previously described [51][52][53] in other diseases and we have linked dysbiosis, gut permeability and intestinal inflammation to adverse outcome in patients with liver cirrhosis. [54] Antihypertensive use was associated with slightly, but significantly elevated CRP levels, which is most likely due to the underlying disease and not to the drug itself, since arterial hypertension is associated with elevated CRP levels [55] and therefore validates the relevance of our findings although sample size is small.…”
Section: Discussionsupporting
confidence: 54%
“…We found that PPI use was associated with increased intestinal in ammation. This has been previously described in the context of other diseases [65][66][67] and we have recently linked dysbiosis, gut permeability and intestinal in ammation to adverse outcome in patients with liver cirrhosis who use PPI. [63] Antihypertensive use was associated with slightly, but signi cantly elevated CRP levels, which is most likely due to the underlying disease and not to the drug itself, since arterial hypertension is associated with elevated CRP levels [68] and therefore validates the relevance of our ndings although sample size is small.…”
Section: Discussionmentioning
confidence: 56%